Core-Shell Co/CoO Integrated on 3D Nitrogen Doped Reduced Graphene Oxide Aerogel as an Enhanced Electrocatalyst for the Oxygen Reduction Reaction - Wang, Meng; Hou, Yuyang; Slade, Robert C. T.; Wang, Jiazhao; Shi, Dongqi; Wexler, David; Liu, Huakun; Chen, Jun (Frontiers in Chemistry, 2016)
Here, we demonstrate that Cobalt/cobalt oxide core-shell nanoparticles integrated on nitrogen-doped (N-doped) three-dimensional reduced graphene oxide aerogel-based architecture (Co/CoO-NGA) were synthesized through a facile hydrothermal method followed by annealing treatment. The unique endurable porous structure could provide sufficient mass transfer channels and ample active sites on Co/CoO-NGA to facilitate the catalytic reaction. The synthesized Co/CoO-NGA was explored as an electrocatalyst for the oxygen reduction reaction, showing comparable oxygen reduction performance with excellent methanol resistance and better durability compared with Pt/C.